From the Desk of Editor - Kumar, Arun (Asian Journal of Medical Sciences, 2021)
Dear All Associated Users of AJMS: It gives us immense pleasure to publish the current issue of AJMS Vol 12 No 1 (2021). We started our journey from 2010 with an online edition of AJMS. Slowly we progressed with the support of our committed and strong team of Editorial board members and launched the printed edition in the year 2015 and we further expanded our publication frequency from quarterly issue to bimonthly issue. With the overwhelming response and support from our users, we now take a leap to publish monthly issue from this year (2021) onwards. With the current expansion of edition, we make it clear that we have not made any compromise in the quality of articles which we publish in AJMS. We have been striving hard to serve the potential authors who has entrusted on us and chosen our journal to publish their manuscripts, making our journal as their journal of choice! On submission, the manuscripts are assigned to editor and section editor for initial review process, followed by assigning the manuscript to three reviewers of which two are internal reviewers and one outside the editorial board (external reviewer). The blind review process in our journal takes six to eight weeks’, sometimes even earlier depending on the reviewers and the decision is made once the review report is submitted to the editor. Sometimes the delay in turnaround time happens which is unavoidable due to late response from reviewers and from the authors. We insist the authors to communicate with the editor soon the review reports are sent to them for revisions. This would further shrink the time of publication from submission. The reviewers and the editorial board members are solely responsible for taking initial decision of the article but the final decision is based on the Editor. The best part of our journal is we respond to each and every author promptly and do not ignore any queries. The details of the journal can be viewed by clicking the links of particular sections- Focus and Scope, Peer Review Process, Open Access Policy, Publication Frequency, Publication Ethics and Publication Malpractice Statement of Asian Journal of Medical Sciences, Duties of Reviewers, Duties of Authors, Indexing of Asian Journal of Medical Sciences can be viewed by this link-https://www.nepjol.info/index.php/AJMS/about Submission Preparation Checklist, Author Guidelines, Plagiarism Policy can be viewed by following this link-https://www.nepjol.info/index.php/AJMS/about/submissions Authors are advised to go through the guidelines and then submit their manuscripts We look forward to further enhance the quality of article in AJMS and we will strive hard to ensure this journal goes global, in the future. Thank you all for your support and entrusting on us. Prof. Dr. Arun Kumar Editor-in-Chief, Asian Journal of Medical Sciences